Gender, Populism, and the QAnon Conspiracy Movement - Bracewell, Lorna (Frontiers in Sociology, 2021)
According to one recent review of the burgeoning interdisciplinary scholarly literature on populism, populism’s “relationship with gender issues remains largely understudied” (Abi-Hassan 2017, 426-427). Of those scholarly treatments that do exist, the lion’s share focus on the role of men and masculinity in populist movements. In this essay, I argue scholarly reflection on the relationship of gender and populism should not be limited to this narrow frame. Through a close examination of the complex gender politics of QAnon, a pro-Trump conspiracy movement that burst into the mainstream of U.S. politics and culture with the onset of the global Coronavirus pandemic, I demonstrate that populist deployments of femininity are as rich, complex, and potent as their deployments of masculinity. QAnon, I argue, is a case study in how femininity, particularly feminine identities centered on motherhood and maternal duty, can be mobilized to engage women in populist political projects. Until scholars of populism start asking Cynthia Enloe’s famous question, “Where are the women?,” in a sustained and rigorous way, phenomena that are integral to populism’s functioning will elude us and our understanding of the relationship of gender and populism will remain partial and incomplete (Enloe 1990).